PENGARUH JUMLAH PENDUDUK MUSLIM, PEMBIAYAAN, DAN BAGI HASIL TERHADAP JUMLAH NOMINAL TABUNGAN NASABAH PADA BANK SYARIAH DI INDONESIA - Amdar, Sudarmin; Ilat, Ventje; Poputra, Agus Tony (Universitas Sam Ratulangi, 2016)
Banking world to be part of a country's economic success. More and more financial institutions that exist in a country, the better the economic turnaround that is therein. The reason the economy was good for people who have more funds can save their money to the bank. While people who need funds to start a business or to add funds to enlarge the business can borrow directly in the bank nearest to the given requirements. The purpose of this study was to determine the Impact of the Muslim population, financing, and for the results of the nominal amount of savings in Islamic Banking in Indonesia. Data collection method used is through surveys and data analysis. Techniques to test the hypothesis by using multiple linear regression analysis processed SPSS version 21. Location research done that is through internet websites and annual financial statements on Islamic Banking in Indonesia, which consists of: PT Bank BRI Syariah, Bank Syariah Bukopin, Bank Syariah Mandiri, Bank Panin Syariah, PT BankÂ Muamalat Indonesia during the year 2009-2013. Muslim population (X1) not significant effect on the nominal amount of savings (Y). Financing (X2) significantly affects nominal amount of savings (Y). For results (X3) no significant effect on the nominal amount of savings (Y). Keywords: impact of the muslim population, financing, and profit sharing the number nominal customer savings